2023
DOI: 10.1186/s12959-023-00458-7
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of venous thrombotic events in patients with interstitial lung disease during hospitalization

Abstract: Background Studies on the incidence of venous thromboembolism (VTE) events in patients with interstitial lung disease (ILD) are limited and the results are inconsistent. The aim of this research was to investigate the incidence and risk factors of VTE in ILD during hospitalization. Materials and methods In this retrospective, cross-sectional, observational study, a total of 5009 patients diagnosed with ILD from January 2016 to March 2022 in our hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…However, the incidence of lower extremity DVT in trauma patients who have received thromboprophylaxis was still as high as 12 ~ 65%[26]. Sun et al [27] found that, even with conventional prevention, the incidence of DVT in multiple trauma patients was as high as 42.08%, of which the incidence of proximal DVT was 6.56% and that of distal DVT was 35.52%. The DVT prevalence in this study was similar to others.…”
Section: Discussionmentioning
confidence: 99%
“…However, the incidence of lower extremity DVT in trauma patients who have received thromboprophylaxis was still as high as 12 ~ 65%[26]. Sun et al [27] found that, even with conventional prevention, the incidence of DVT in multiple trauma patients was as high as 42.08%, of which the incidence of proximal DVT was 6.56% and that of distal DVT was 35.52%. The DVT prevalence in this study was similar to others.…”
Section: Discussionmentioning
confidence: 99%
“…However, the incidence of lower extremity DVT in trauma patients who have received thromboprophylaxis was still as high as 12 ~ 65% [ 23 ]. Sun et al [ 24 ] found that, even with conventional prevention, the incidence of DVT in multiple trauma patients was as high as 42.08%, of which the incidence of proximal DVT was 6.56% and that of distal DVT was 35.52%. The DVT prevalence in this study was similar to others.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective clinical study found that the incidence of VTE in patients with CTD-ILD was 20% [ 11 ]. Although the subtype of ILD is an independent risk factor affecting the development of VTE in patients with ILD [ 12 ], existing clinical studies on the occurrence of VTE in patients with ILD have mainly focused on IPF, and there is a lack of large-scale multicenter clinical statistical studies on the clinical characteristics and risk factors for the occurrence of VTE in patients with CTD-ILD, and exploratory studies at home and abroad on the mechanism of thrombosis in this type of patients are equally inadequate.…”
Section: Introductionmentioning
confidence: 99%